Assessment of calcium and zinc accumulation in cultivated and wild apples. (28th March 2017) - Liao, Liao; Fang, Ting; Ma, Baiquan; Deng, Xianbao; Zhao, Li; Han, Yuepeng
Abstract: BACKGROUND: Apple is one of the staple fruits worldwide which are a good source of mineral nutrients. However, little is known about genetic variation for mineral nutrition in apple germplasm. In this study, the calcium and zinc contents in mature fruits of 378 apple cultivars and 39 wild relatives were assessed. Mineral concentrations were quantified using flame atomic absorption spectroscopy (FAAS). RESULTS: Both calcium and zinc accumulation showed great variation among accessions tested. Overall, wild fruits were significantly richer in zinc than cultivated fruits, while the average concentration of calcium was similar between cultivated and wild fruits. The difference in zinc concentration between wild and cultivated fruits may be an indirect result of artificial selection on fruit characteristics during apple domestication. Moreover, calcium concentration in fruit showed a decreasing trend throughout fruit development of apple, while zinc concentration in fruit displayed a complex variation pattern in the late stages of fruit development. CONCLUSION: The finding of a wild genetic variation for fruit calcium and zinc accumulation in apple germplasm could be helpful for future research on genetic dissection and improvement of calcium and zinc accumulation in apple fruit. © 2017 Society of Chemical Industry